EVALUASI RASIONALITAS PENGOBATAN HIPERTENSI DI PUSKESMAS PELAMBUAN BANJAR MASIN TAHUN 2017 - Saftia Aryzki; Noor Aisyah; Hesti Hutami; Besty Wahyusari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Irrational use of drugs is still found in Puskesmas which is the First Level Health Facilities. The use of irrational drugs based on appropriate drugs and precise indications. In the use of various types of drugs there may be an irrationality of treatment, one of which is hypertension.This study aims to determine the antihypertensive drugs used in Pelambuan Puskesmas Banjarmasin and to determine the percentage of rationality of hypertension treatment at Pelambuan Puskesmas Banjarmasin. evaluating the rationale for the use of antihypertensive drugs that include the accuracy of indication, drug, dose, patient, mode of administration, and duration of administration in hypertensive patients at Puskesmas Pelambuan Banjarmasin during 2017. This type of research was descriptive non-experimental research with retrospective data retrieval based on medical records of hypertensive patients in 2017. The population in this study amounted to 333 medical records and the number of samples that met the inclusion and exclusion criteria as much as 37 medical records. The tools / instruments in this study were observation sheets and interview sheets. The results of the research on antihypertensive drugs used in Pelambuan Banjarmasin Health Center were amlodipine, nifedipine, captopril, lisinopril. The results of the evaluation of the rationality of the use of antihypertensive drugs were seen based on the exact indication criteria as many as 18 patients (48,65%), right medication as many as 18 patients (48,65%), right dose of 17 patients (45,95%), right patients as many as 33 patients (89,19%), the exact method of administration was 31 patients (83,79%), and the exact duration of administration was 22 patients (59,46%).